Introducción a la base de datos en Oracle - Briseño, Jessica (My University, 1994)
The information in one table may be related to the information in another. Each employee in EMP, for example, has a department number (DEPTNO) that refers to a department number in a table named DEPT. The ability to relate information in one table to another allows you to organize information in separate, manageable units.
Keywords: table; information; ability; commands; system